Analysis of motor vehicle taxpayer compliance at the Batang regency regional tax service unit - Kurniawati, Emaya; Rajayana, Ades; Hidayat, Guruh Mulia (Institute of Computer Science (IOCS), 2024)
From year to year the number of motorized vehicle ownership is increasing with the increase in the number of motorized vehicles expected to increase the amount of regional revenue, especially in the field of motor vehicle tax. In the UPPD of Batang Regency in the last five years there has been a decrease in motor vehicle tax revenue, this study aims to determine what factors affect the compliance of motor vehicle taxpayers in Batang Regency. The research was conducted on Bermotro vehicle taxpayers in Batang Regency with a total of 100 respondents. The research method used is quantitative research with an explanatory research approach. Data processing was carried out with the Smart PLS application. The results showed that the variables of attitude, subjective norms, behavioral control and intention had a positive and significant effect on compliance intentions.